Evaluating interviews which search for the truth with suspects: but are investigators’ self-assessments of their own skills truthful ones? - Walsh, Dave (Psychology, crime & law, 2017)
Self-evaluation of one’s own performance has been found in prior research to be an enabler of professional development. The task of evaluation is also a core component of a model of the investigative interviewing of victims, witnesses and suspects, being increasingly used throughout the world. However, it remains the case that there has been little research as to how practitioners approach the task itself. The present study examined the topic through the lens of observing how effectively 30 real-life investigators in the UK undertook evaluation of their interviews, representing almost the entire investigative frontline workforce of a small law enforcement agency in this country. Using an established scale of measurement, both investigators’ and an expert’s ratings of the same sample of interviews were compared across a range of tasks and behaviours. It was found that in almost all the assessed behaviours, requiring of the investigators to provide a self-rating, their scores tended to significantly outstrip those applied to the sample by the expert. Reasons are explored for the investigators’ overstated assessments. Implications for practice are then discussed.